The Effectiveness Of The Administration Of Beet Juice And Honey Against Increased Hemoglobin Levels In Nursing Mothers - Samsa Qomariyah; Novita Novita (CV. Inara, 2023)
WHO in 2020, said some 295,000 women worldwide lost their lives during and after pregnancy and childbirth. Africa, sub-Saharan and South Asia account for around 86% of all maternal deaths worldwide. MMR in Indonesia in 2020 is 230 per 100,000 live births. Causes of maternal death are bleeding, hypertension, infection, prolonged labour, abortion, CED and anemia (Hb <11gr). The prevalence of anemia in pregnant and lactating women in Indonesia is 48.9%. The impact of anemia on pregnant women will occur during pregnancy, childbirth and the postpartum period. Knowing the effectiveness of giving beetroot juice and honey to increase hemoglobin levels in nursing mothers. Quasy Experiment with Pretest Posttest With Control Group Design The sample in this study were lactating mothers with anemia who were registered at the KIA PMB Samsa Qomariyah register in May-October 2022 as many as 40 people, the sampling technique was total sampling. The average HB level in the intervention group was 10.175 gr/dl pretest and 10.865 gr/dl posttest. The average HB level in the control group was 11.250 gr/dl pretest and 11.275 gr/dl posttest. Beetroot juice and honey are effective in increasing hemoglobin levels in lactating mothers with a p.value of 0.000 (p <0.005). Beetroot juice and honey are effective in increasing hemoglobin levels in nursing mothers. It is expected that breastfeeding mothers consume vegetables and fruit that contain lots of iron and vitamin C to increase HB levels and prevent anemia.